Number of prior negative screening outcomes does not influence future risk of breast cancer - Lilleborge, Marie (Eur J Epidemiol, 2020)
We questioned whether a history of negative screening outcomes could be used to predict breast cancer risk, and thus be used as a potential factor for stratification of mammographic screening. Data from the Norwegian population based breast cancer screening program, BreastScreen Norway, was used to estimate cumulative hazard rates for breast cancer by number of prior negative screening outcomes among participants from 1995 through 2016. We followed three age cohorts of women, who started screening at age 50–54, 55–59, and 60–64 years. Further, we estimated the absolute and relative risk of breast cancer by number of prior negative screening outcomes. The cumulative hazard curves were parallel for all numbers of negative screening outcomes for all age cohorts. The absolute risk of breast cancer increased with number of negative screening outcomes for the youngest age cohort. For the oldest age cohorts, the absolute risk was stable during the screening period and decreased thereafter. The number of negative screening outcomes was not associated with risk of breast cancer, adjusted for age, percent screening attendance and calendar years (HR 1.00, 95% CI 0.98–1.02). Our results suggest that the number of negative screening outcomes does not predict breast cancer risk among participants in BreastScreen Norway.